Detection and Identification of Bacteria by Gas Chromatography - Henis, Y. (1966)
Ether extracts of cultures of 29 strains representing 6 species of Bacillus, and of individual strains of Escherichia coli, Aerobacter aerogenes, and Pseudomonas aeruginosa were examined in a gas chromatograph by use of flame ionization and electron capture detectors. Among the products detected were compounds with the chromatographic characteristics of acetic, propionic, and butyric acids, ethyl alcohol, diacetyl, acetoin, and 2,3-butanediol. The differences in peak areas of the various products formed by the bacteria were determined statistically for the chromatograms obtained with the two detectors, and the peaks were arranged in order of decreasing areas to yield a signature for each bacterial strain. Different signatures were obtained for the various genera and species and for strains of the same species. B. licheniformis, B. subtilis, and A. aerogenes formed significant quantities of a number of volatile compounds, and qualitative and quantitative differences between strains were noted. The electron capture detector was particularly sensitive to diacetyl and acetoin as well as to unknown compounds. By use of this detector, the presence of 5 pg of diacetyl and 20 pg of acetoin could be demonstrated. The quantity of acetoin detected in B. subtilis and B. licheniformis cultures was present in as little as 6.3 × 10(-3) μliters of medium.